Carbamazepine Vs Valproate and Cognitive Function - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Effects of carbamazepine vs valproate on cognitive functioning in patients with previously unmedicated epilepsy were evaluated in a prospective, randomized, double-blind Veterans Affairs multicenter study.